2014
DOI: 10.1002/ar.22981
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Sarcomeric Proteins During Myofibril Assembly in Cultured Mouse Primary Skeletal Myotubes

Abstract: It is important to understand how muscle forms normally in order to understand muscle diseases that result in abnormal muscle formation. Although the structure of myofibrils is well understood, the process through which the myofibril components form organized contractile units is not clear. Based on the staining of muscle proteins in avian embryonic cardiomyocytes, we previously proposed that myofibrils formation occurred in steps that began with premyofibrils followed by nascent myofibrils and ending with mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
57
1
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 45 publications
6
57
1
2
Order By: Relevance
“…Earlier studies of cardiac myofibrillar assembly used non-human (Dabiri et al, 1997; Ehler et al, 1999; Ferrari et al, 1998; Gerull et al, 2002; Schultheiss et al, 1990; Tokuyasu and Maher, 1987; Tullio et al, 1997; van der Ven et al, 2000) or non-cardiac cell (Hill et al, 1986; Miller et al, 2003; Sanger et al, 2009; White et al, 2014) models wherein de novo sarcomere assembly dynamics have not been easily observed. Here we use live imaging of genetically modified human stem cell derived cardiomyocytes to demonstrate that sarcomere assembly is a highly dynamic and coordinated process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies of cardiac myofibrillar assembly used non-human (Dabiri et al, 1997; Ehler et al, 1999; Ferrari et al, 1998; Gerull et al, 2002; Schultheiss et al, 1990; Tokuyasu and Maher, 1987; Tullio et al, 1997; van der Ven et al, 2000) or non-cardiac cell (Hill et al, 1986; Miller et al, 2003; Sanger et al, 2009; White et al, 2014) models wherein de novo sarcomere assembly dynamics have not been easily observed. Here we use live imaging of genetically modified human stem cell derived cardiomyocytes to demonstrate that sarcomere assembly is a highly dynamic and coordinated process.…”
Section: Discussionmentioning
confidence: 99%
“…Our current understanding of sarcomere assembly is incomplete, based mostly on observations from immunohistochemistry analysis in vertebrate models of either cardiomyocytes or skeletal muscle cells with limited perturbations to critical sarcomeric protein components (Rhee et al, 1994; Sanger et al, 2009; Schultheiss et al, 1990; White et al, 2014). Cardiomyocytes are thought to initiate myofibrillar assembly at the cell periphery from pre-myofibrils consisting of non-muscle myosin II (NMM II) and α-actinin-2 fibers, providing a template for subsequent recruitment of titin, α-and/or β-cardiac myosins to form mature myofibrils (Dabiri et al, 1997; Rhee et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…A scaffold of actin filaments, integrating α-actinin and titin, seems to be the core component for the subsequent integration of M-band modules, sarcomeric myosin and accessory proteins Sanger et al, 2010;Van der Ven et al, 1999;White et al, 2014). In vivo, primary sarcomere assembly occurs close to the cell membrane and seems to involve as yet poorly understood links to the membrane cytoskeletal system.…”
Section: Introductionmentioning
confidence: 99%
“…Although this model was first developed from observations of antibody localization in cultured avian cardiomyocytes, it was tested subsequently with time‐lapse imaging in cultures of live cardiomyocytes expressing green fluorescent protein‐alpha‐actinin [Dabiri et al, ]. Antibody localization results have also confirmed this model of myofibrillogenesis in avian precardiac cardiac explants [Du et al, ], in embryonic avian hearts fixed in situ [Du et al, ], in zebrafish [Sanger et al, ], and in cultured mouse primary skeletal muscle cells [White et al, ]. Recent support for the premyofibril model was reported by Liu et al [] using a novel form of microscopy, i.e., two‐photon excited fluorescence‐second harmonic generation, or TREF‐SHG, to follow the incorporation of unlabeled myosin II filaments onto premyofibrils to form nascent myofibrils in living neonatal rat cardiomyocytes.…”
Section: Introductionmentioning
confidence: 99%